The Influence of Deliberative Thinking, Mental Budgeting, and Self-Control on the Financial Well-Being of Generation Z in Jakarta Special Capital Region - Iif Latifah Sukriah; Ummu Salma Al Azizah; Elmy Nur Azizah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Generation Z in Indonesia, particularly in Jakarta, has grown up in a digital environment that promotes highly consumptive lifestyles through trends such as Fear of Missing Out (FOMO) and You Only Live Once (YOLO), making them more vulnerable to financial instability and lower financial well-being. This study examines the effects of deliberative thinking, mental budgeting, and self-control on the financial well-being of Generation Z in Jakarta. A quantitative research design was employed using a survey of 400 respondents born between 1997 and 2012, selected through probability sampling based on the Slovin formula. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that deliberative thinking (β = 0.168, t = 2.076, p = 0.019), mental budgeting (β = 0.233, t = 3.123, p = 0.001), and self-control (β = 0.368, t = 4.228, p < 0.001) each have a positive and significant effect on financial well-being. Among these variables, self-control demonstrates the strongest influence. Collectively, the three predictors explain 48.1% of the variance in financial well-being (R² = 0.481). These findings highlight the importance of strengthening self-control and mental budgeting practices, alongside promoting deliberative decision-making, to enhance the financial well-being of young adults in the face of increasing digital economic challenges.